APPLICATION OF FISHBONE DIAGRAM IN USING ROOT CAUSE ANALYSIS (RCA) FOR DEVELOPING OF REVENUE AND EXPENDITURE SYSTEM IN MANUFACTURING COMPANY - Fatmaria Tantri, Sinta; Eltivia, Nurafni; Djajanto, Ludfi (Yayasan Education and Social Center, 2024)
This study aims to identify the root problems in developing income and expenditure systems in the PT ABC. This research uses qualitative methods with the Root Cause Analysis approach. The issues that arise in the company will be analyzed using the Fishbone Diagram. The result of this study explains that some problems occur in the company. The procedures, business processes, income, and expenditure in the enterprise are still done manually, so it takes a long time to analyze the factors of Man (user), Material (material/supporting documents), Machine (tools used), and Method (procedures/systems running). Based on the result of this study, PT ABC should have a website that can be used to process the cycle of income and expenses in real time. In this case, website design will be carried out to make it easier for companies to archive, create supporting documents, and report income and expenses. This finding will help PT ABC strengthen its internal control and increase the effectiveness of the company's business process. The difference between this research and previous research is that it uses a fishbone diagram approach to dig into the roots of problems that occur in companies. In the last research, no one had used a rooting approach and focused only on system development, so the issues that occurred needed to be described in detail. The limitation of this research is its focus on the root cause analysis of the revenue and expenditure cycle in manufacturing companies